Penerapan Metode Role Playing pada Kemampuan Berpikir Kritis Siswa Kelas V SD Islam Al-Mizan Surabaya dalam Materi Penerapan Nilai-Nilai Pancasila di Lingkungan Keluarga - Fa'izah, Wardah Putri; Larasati, Diyas Age; Popiyanto, Yudha (Indo-MathEdu Intellectuals Journal, 2025)
The effective experiential learning type is role playing, where children play roles in presenting social or psychological problems to understand and develop skills in problem-solving. The purpose of this study is to understand the application of the role playing method on the critical thinking skills of fifth-grade students at Al-Mizan Islamic Elementary School in Surabaya regarding the application of Pancasila values in the family environment. The method used in this study is qualitative. Data collection techniques include tests, observation sheets, interviews, and documentation. Data analysis uses qualitative data analysis with the stages of data reduction, data presentation, and conclusion drawing. The results of this study show that 81.25% reached the very good category with 13 students, 12.5% reached the good category with 2 students, and 6.25% reached the sufficient category with 1 student. Although there were some difficulties in the learning process, those 16 students are still considered complete because they have demonstrated good ability and understanding. It can be concluded that the learning process has been effective in improving the abilities and understanding of the students.